The Frith prescribing guidelines for people with intellectual disability - Bhaumik, Sabyasachi; Branford, David; Barrett, Mary, Dr.; Gangadharan, Satheesh Kumar (Chichester, West Sussex ; Hoboken, NJ : Wiley-Blackwell, 2015)
The Frith Prescribing Guidelines for People with Intellectual Disability provides comprehensive guidance on prescribing for patients with intellectual disability, as well as general information on the clinical care of this important population. The guidelines have been conceived and developed by clinicians working in intellectual disability services. They are based on both the latest evidence and expert opinion to provide a consensus approach to prescribing as part of a holistic package of care, and include numerous case examples and scenarios. New to this edition are improved coverage of children and the role of primary care teams. The Frith Prescribing Guidelines for People with Intellectual Disability, Third Edition, is a practical guide for busy clinicians, as well as a valuable reference for all primary and secondary health care professionals caring for people with intellectual disability.
Intellectual disability / David Branford & Sabyasachi Bhaumik -- Prescribing practice / David Branford & Sabyasachi Bhaumik -- Physical and health monitoring / David Branford & Sabyasachi Bhaumik -- Epilepsy / Reza Kiani -- Dementia in people with intellectual disability / Satheesh Kumar & Amala Jesu -- Eating and drinking difficulties / Jenny Worsfold, Nicky Calow & David Branford -- Sleep disorders / Reza Kiani -- Women's health issues -- Nyunt Tin & Julia Middleton -- Sexual offending / John Devapriam, Pancho Ghatak, Sabyasachi Bhaumik, David Branford, Mary Barrett & Sayeed Khan -- Autism spectrum disorders / Mary Barrett & Elspeth Bradley -- Attention deficit hyperactivity disorder (ADHD) / Karen Bretherton -- Aggressive behavior / David Branford & Sabyasachi Bhaumik -- Self-injurious behaviour / Asit Biswas & Sabyasachi Bhaumik -- Anxiety disorders / Avinash Hiremath, Sabyasachi Bhaumik & Khalid Nawab -- Depression / Avinash Hiremath, Shweta Gangavati & Mary Barrett -- Bipolar affective disorder / Desari Mohan Michael, David Branford & Mary Barrett -- Schizophrenia / Avinash Hiremath, Amala Jesu & Saduf Riaz -- Alcohol use disorders / Helen Miller -- Personality disorders / Regi Alexander & Sabyasachi Bhaumik -- Discussion case studies with suggested answers -- Appendix -- Index.
Originally published as Frith prescribing guidelines for adults with learning disability.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Mental illness -- Chemotherapy; Developmental disabilities -- Chemotherapy; Intellectual Disability -- complications; HEALTH & FITNESS -- Diseases -- General; MEDICAL -- Clinical Medicine; MEDICAL -- Diseases; MEDICAL -- Evidence-Based Medicine; MEDICAL -- Internal Medicine; Mental Disorders -- drug therapy; Intellectual Disability -- complications; Mentally Disabled Persons -- psychology; Psychotropic Drugs -- administration & dosage; Electronic books; Practice Guideline